Key performance indicators : developing, implementing, and using winning KPIs. - Parmentier, David, ....- (New jersey : Wiley, 2007)
Breathtaking in its simplicity and profound in its impact, Key Performance Indicators (KPI) distills the balanced scorecard process into twelve logical steps, equipping users with an implementation resource kit that includes questionnaires, worksheets, workshop outlines, and a list of over 500 performance measures. Author David Parmenter provides you with everything you need to master and implement a KPI-driven strategy. Chapter 1. Introduction. Key Result Indicators. Key Performance Indicators. Management Models that Have a Profound Impact on KPIs. Definitions. Chapter 2. Foundation Stones for Implementing Key Performance Indicators. Four Foundation Stones Guiding the Development and Use of KPIs. Defining Vision, Mission, and Strategy. How to Implement Winning KPIs in 16 Weeks. Chapter 3. Developing and Using KPIs: A 12-Step Model. Step 1. Senior Management Team Commitment. Step. 2. Establishing a "Winning KPI" Project Team. Step 3. Establish a "Just Do It" Culture and Process. Step 4.
Setting Up a Holistic KPI Development Strategy. Step 5. Marketing the KPI System to All Employees. Step 6. Identifying Organization-Wide Critical Success Factors. Step 7. Recording Performance Measures in a Database. Step 8. Selecting Team-Level Performance Measures. Step 9. Selecting Organizational "Winning KPIs". Step 10. Developing the Reporting Framework at All Levels. Step 11. Facilitating the Use of Winning KPIs. Step 12. Refining KPIs to Maintain their Relevance. Chapter 4. KPI Team Resource Kit. Using This Resource Kit. Step 1 Worksheet. Senior Management Team Commitment. Step 2 Worksheet. Establishing a Winning KPI Team. Step 3 Worksheet. Establish a "Just Do It" Culture for This Project. Step 4 Worksheet. Setting Up a Holistic KPI Development Strategy. Step 5 Worksheet. Marketing the KPI System to All Employees. Step 6 Worksheet. Identifying Organization-Wide CSFs. Step 7 Worksheet. Comprehensive Recording of Measures within the Database. Step 8 Worksheet. Selecting Team performance
Measures. Step 9 Worksheet. Selecting Organization-Wide "Winning KPIs". Step 10 Worksheet. Developing Display, Reporting and Review Frameworks at All Levels. Step 11 Worksheet. Facilitating the Use of KPIs. Step 12 Worksheet. Refining and Modifying KPIs to Maintain Their Rlevance. Chapter 5. Templates for Reporting Performance Measures. Reporting Key Result Indicators in a "Dashboard" to the Board. Reporting Performance Measures to Management. Reporting Performance Measures to Staff. Graph Format Examples. Chapter 6. Facilitator's Resource Kit. Remember the Fundamentals. Appendix. Performance Measures Database. Index.